15.6k views
2 votes
Solve 7x(-2+3)+(-5-2)

User MCKapur
by
6.1k points

2 Answers

6 votes
You should follow the order of operations to solve 7x(-2+3)+(-5-2)

First, we solve the problems that is inside the parenthesis
7x(-2+3)+(-5-2)=
7x(1)+(-7)=
7x1-7
Then we do the multiplication problem
7x1-7=
7-7=0
We finally do the remaining problem

The answer to your problem is 0

I hope this helps
User Phob
by
5.8k points
0 votes
7x(-2+3)+(-5-2)
= 7x(1)+(-7)
= 7+(-7)
= 7-7
= 0
User Ross Larson
by
6.5k points